THU0508 Sparing Methotrexate Results in a Less Stringent Control of Plasma Cell and Immunoglobulin Free Light Chain Production in Seropositive Patients with Rheumatoid Arthritis. (10th June 2014) - Saunders, U.; Fassbinder, T.; Becker, H.; Jung, E.; Mickholz, E.; Willeke, P.; Schlüter, B.; Jacobi, A.M.
Abstract : Background: Clinical trials revealed that tumor necrosis factor alpha (TNF-α) blockade is more effective if administered with concomitant methotrexate (MTX). Objectives: Based on an observation made when studying B cell subsets in patients with seropositive (sp) rheumatoid arthritis (RA) this study aimed to investigate the influence of MTX on late stages of B cell development. Methods: Peripheral blood samples of 78 spRA patients divided into four treatment groups (MTX: n=23, TNF-α-inhibitor: n=23, MTX/TNF-α-inhibitor: n=17 and patients without MTX/TNF-α-inhibitor: n=15) were obtained and lymphocyte cell subsets were analyzed by multiparameter flow cytometry. To investigate the effect of MTX on B cell proliferation and differentiation cell culture assays were performed. Results: SpRA patients treated with MTX as monotherapy or in combination with TNF blockade exhibited significant lower frequencies and numbers of CD27 ++ CD38 ++ plasmablasts (PB)/plasma cells and a lower serum concentration of free light chains (FLC) compared to patients on anti-TNF-α monotherapy (Table 1 ). MTX had no effect on in vitro proliferation, differentiation, and survival of purified B cells, but patients taking MTX showed significantly lower numbers of CD4 + CD45RO + memory (288 (117-876); p<0.01) and CD4 + CD44 + CD62L low effector T cells (79 (11-315); p<0.05) compared to patients not on MTX (450 (101-1916); 123 (30-629), respectively). Memory (rs =0.3, p<0.001) and effector (rs =0.33, p<0.005) CD4 + T cell numbers correlated significantly with PB counts, as did FLC (rs =0.37, p<0.001) and MCV (rs =0.46, p<0.001) but not CCP antibody levels. Although there was no significant correlation of PB and the disease activity (DAS28), soluble surrogate markers of B cell activation as serum MCV (rs =0.501, p<0.0002) and CCP (rs =0.296, p<0.03) antibody and FLC levels (rs =0.35, p<0.005) showed a significant correlation with DAS28. Conclusions: Adding to the beneficial effect of TNF-α inhibitors, MTX seems to affect late stages of B cell activation and differentiation in spRA. It does not act directly as we recently described for mycophenolic acid. For MTX we postulate an indirect mechanism of action for instance by influencing the activation and differentiation of T helper cells. The findings argue for concomitant use of MTX with TNF-α inhibitors to increase therapeutic efficacy. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2207